Rethinking sexual violence labels: exploring the impact of ‘victim’ and ‘survivor’ discourse - O’Shea, Brittany; Feicht, Rebecca; Brown, Marion; Numer, Matthew (European Journal of Psychotraumatology, 2024)
Background: Universities’ responses to sexual violence have faced scrutiny for their lack of proactiveness and their failure to address campus socio-cultural norms that contribute to rape myth acceptance. The labels victim and survivor play a crucial role in shaping attitudes toward sexual violence, but there is limited research on how university students perceive these labels. Objective: This paper explores sexual violence labels and their role in perpetuating rape culture. Undergraduate university students’ beliefs on using the label survivor instead of victim to describe someone who has experienced sexual violence were examined to consider how these labels create societal discourse on sexual violence. Method: The study draws on qualitative data collected from undergraduate students in Canada and the United States through open-response questions in an interactive textbook. Data were analysed and interpreted using a multi-method approach that combined principles of Critical Discourse Analysis and Feminist Poststructuralism. Direct quotes and word clouds from participants’ responses are used as evidence and to visually display discourse. Results: Findings revealed that participants recognised the negative societal discourses associated with the label victim and supported using survivor to challenge perceptions of sexual violence. Despite this, participants expressed hesitancy to adopt the label survivor because of the potential negative implications, such as the label promoting the allocation of individual blame, increasing barriers to justice, and reducing the perceived severity of sexual violence. Conclusions: This study underscores the complexities of sexual violence labels, the influence of language in shaping societal perceptions, and the need for a more comprehensive and equitable approach to responding to sexual violence. Dichotomy of Labels and Nuanced Perceptions: Sexual violence labels shape identity perceptions. Participants dichotomised the labels victim and survivor, associating one with negative attributes and the other with positive attributes. However, nuanced views of how people perceive and identify with these labels challenge distinct categories. Victims being negatively perceived, while survivors are admired for their resiliency highlights complexities in societal expectations that may not fully address the underlying determinants of sexual violence.Role of Language in Reproduction of Rape Culture: Poststructuralist theories emphasise the role of language in the production and maintenance of discourse. The study shows that victim discourse is steeped in rape myths. The historical discourse surrounding the label may contribute to the perpetuation of negative attitudes and behaviours toward victims of sexual violence. The emergence of the label survivor reflects a societal shift, but findings suggest this may lead to societal complacency towards sexual violence.Spectrum of Severity and Societal Empathy: Participants’ understanding of sexual violence as a spectrum of severity may lead to unequal levels of empathy and support. This discourse creates positions of dominance and oppression, potentially marginalising certain groups who are disproportionately affected by sexual violence. The study highlights how severity discourse can influence institutional agendas and may result in political and institutional neglect of sexual violence. Dichotomy of Labels and Nuanced Perceptions: Sexual violence labels shape identity perceptions. Participants dichotomised the labels victim and survivor, associating one with negative attributes and the other with positive attributes. However, nuanced views of how people perceive and identify with these labels challenge distinct categories. Victims being negatively perceived, while survivors are admired for their resiliency highlights complexities in societal expectations that may not fully address the underlying determinants of sexual violence. Role of Language in Reproduction of Rape Culture: Poststructuralist theories emphasise the role of language in the production and maintenance of discourse. The study shows that victim discourse is steeped in rape myths. The historical discourse surrounding the label may contribute to the perpetuation of negative attitudes and behaviours toward victims of sexual violence. The emergence of the label survivor reflects a societal shift, but findings suggest this may lead to societal complacency towards sexual violence. Spectrum of Severity and Societal Empathy: Participants’ understanding of sexual violence as a spectrum of severity may lead to unequal levels of empathy and support. This discourse creates positions of dominance and oppression, potentially marginalising certain groups who are disproportionately affected by sexual violence. The study highlights how severity discourse can influence institutional agendas and may result in political and institutional neglect of sexual violence.
Keywords: Bibliographie; Nettoyer